2020
DOI: 10.1371/journal.pone.0232536
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell-derived factor 1 regulates in vitro sperm migration towards the cumulus-oocyte complex in cattle

Abstract: Sperm migration towards an oocyte in the female reproductive tract is an important step for successful fertilization. Although several sperm-chemotactic factors have been identified in mammals, it is unclear whether these chemoattractants contribute to sperm migration towards an oocyte that is the final destination for sperm. Furthermore, chemoattractants for bovine sperm are still undiscovered even though the follicular fluid attracts sperm in cattle. Here, we demonstrated that a single bovine cumulus-oocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Both the follicular fluid and the cumulus cells are known to secrete a variety of chemokines that promote sperm hyperactivity and increase sperm motility following receptor binding [ 35 , 36 ]. One of the reported cytokines, CXCL12, is able, moreover, to build a complex with CXCR4 (the CXCL12–CXCR4 complex), which has been described as one of the main mechanisms to promote sperm chemotaxis towards the COC [ 22 ], although its location in the participating cell types might also represent a specific anchoring mechanism during fertilization, perhaps even selecting/favoring only the capacitated spermatozoa to engage in ZP-binding and further fertilization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the follicular fluid and the cumulus cells are known to secrete a variety of chemokines that promote sperm hyperactivity and increase sperm motility following receptor binding [ 35 , 36 ]. One of the reported cytokines, CXCL12, is able, moreover, to build a complex with CXCR4 (the CXCL12–CXCR4 complex), which has been described as one of the main mechanisms to promote sperm chemotaxis towards the COC [ 22 ], although its location in the participating cell types might also represent a specific anchoring mechanism during fertilization, perhaps even selecting/favoring only the capacitated spermatozoa to engage in ZP-binding and further fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that CXCL12 is produced in the cumulus cells cytoplasm, from where it may act as a sperm chemoattractant prior to fertilization. Previous studies reported that CXCL12 is locally produced by cumulus cells from human [ 21 ], cattle [ 22 ], and sheep oocytes [ 23 ]. Furthermore, besides its role in oocyte maturation, a recent study in cattle [ 22 ] suggested that a single COC has the ability to attract spermatozoa towards the oocyte, pointing to CXCL12 as the main sperm chemoattractant candidate, which would interact with its receptor (CXCR4) if localized in the spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the quality of mitochondrial function between agglutinated and unagglutinated sperm, the mitochondrial membrane potential (MMP) of sperm was evaluated by 5,5′,6,6′-tetrachloro-1,1′,3,3′-tetraethylbenzimidazolylcarbocyanine iodide (JC-1) staining using a commercially available kit as reported previously (MitoProbe TM JC-1 Assay Kit, Thermo Fisher Scientific) [ 20 ]. Briefly, sperm suspension was incubated in non-capacitation medium for 0, 5 or 24 h at 38.5 °C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the study of sperm behavior and its ability to react to external stimuli could be used as an indicator of sperm quality, and could help to predict the fertility of a given seminal sample, assisted by computer automation. One of the most studied mechanisms involved in sperm guidance is chemotaxis, or the directed movement of sperm in response to a chemical gradient [ 23 , 24 ]. Due to the lack of a specific tool in both commercial and open source systems, the first version of OpenCASA included a module for sperm guided movement analysis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%